Монодрама як жанр: теоретико-історичний аспект (стаття друга) - Бортнік, Жанна Іванівна; Bortnik, Zhanna I. (Східноєвропейський національний університет ім. Лесі Українки, 2013)
У статті розглядаються етапи розвитку монодрами, визначаються основні літературно-історичні чинники, що зумовили модифікацію монодрами у кінці ХХ – на початку ХХІ ст. Авторка статті поєднала історичний підхід до жанру з теоретичним, виокремила визначальні жанрові риси приналежності драматичного твору до жанру монодрами.

In the article the periods of monodrama's development were considered, the main literary-historical aspects which caused the modification of monodrama in the end of XX century were defined. The author of the article combines historical approach to the genre of theoretical allocated genre defining traits belonging to the genre of monodramа: author creates a single subject of an action, the subjects of speech exemplifies inner psychological reality of a single action subject, the idea of monodrama is implemented through co-creation with reader.
Monodrama as a genre: theoretical and historical aspects (second article)
Keywords: монодрама; монолог; жанр; персонаж; конфлікт; автор; сюжет; monologue; monodrama; genre; character; conflict; author; plot